LANGUAGE DEVELOPMENT IN STUDY ABROAD (SA) CONTEXT AND RELATIONSHIP WITH INPUT AND INTERACTION IN SLA - suryani suryani (Universitas Islam Negeri Banda Aceh, 2015)
Language learning can occur anytime and anywhere (context). In term of context, language learning can take place whether at home context or at a study abroad context. This article presents the necessary background to existing literature and previous research about language development in various contexts, more specifically in a study abroad (SA) context. Language learners who are studying abroad can lead to language development from a number of perspectives. Research findings revealed that language development can take a variety of forms including grammar, vocabulary, fluency, communicative skill, etc. These research findings will be reviewed in order to have a clear understanding about this issue. Then, this article continues to give a brief explanation on the role of input and interaction in SLA with some views on it.